2023
DOI: 10.1038/s41586-023-05878-z
|View full text |Cite
|
Sign up to set email alerts
|

Momentum transfer from the DART mission kinetic impact on asteroid Dimorphos

Abstract: The NASA Double Asteroid Redirection Test (DART) mission performed a kinetic impact on asteroid Dimorphos, the satellite of the binary asteroid (65803) Didymos, at 23:14 UTC on 26 September 2022 as a planetary defence test1. DART was the first hypervelocity impact experiment on an asteroid at size and velocity scales relevant to planetary defence, intended to validate kinetic impact as a means of asteroid deflection. Here we report a determination of the momentum transferred to an asteroid by kinetic impact. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 45 publications
6
96
1
Order By: Relevance
“…Initial analysis of observations of the system reveals a reduction in the secondary's tangential (along-track) component of orbital velocity by about 2.7 mm s −1 (Cheng et al 2023). This corresponds to a momentum enhancement factor in the range of 2.2-4.9, depending on the unmeasured mass of Dimorphos, indicating the ejecta launched by the impact had a larger contribution to the change in momentum than the actual DART impact itself (Cheng et al 2023). The analysis by Cheng et al (2023) serves as a good first look into the post-impact dynamics of Didymos, which will be measured accurately in detail by the ESA Hera mission in 2027 (Michel et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial analysis of observations of the system reveals a reduction in the secondary's tangential (along-track) component of orbital velocity by about 2.7 mm s −1 (Cheng et al 2023). This corresponds to a momentum enhancement factor in the range of 2.2-4.9, depending on the unmeasured mass of Dimorphos, indicating the ejecta launched by the impact had a larger contribution to the change in momentum than the actual DART impact itself (Cheng et al 2023). The analysis by Cheng et al (2023) serves as a good first look into the post-impact dynamics of Didymos, which will be measured accurately in detail by the ESA Hera mission in 2027 (Michel et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The impact altered the trajectory of Dimorphos around Didymos, reducing the orbit period by around 33 minutes (Thomas et al 2023). Initial analysis of observations of the system reveals a reduction in the secondary's tangential (along-track) component of orbital velocity by about 2.7 mm s −1 (Cheng et al 2023). This corresponds to a momentum enhancement factor in the range of 2.2-4.9, depending on the unmeasured mass of Dimorphos, indicating the ejecta launched by the impact had a larger contribution to the change in momentum than the actual DART impact itself (Cheng et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When viewed 90°from the axis and spacecraft direction (as at the time of impact in 2022 September), the edges of the cone appear as two "wings" separated by a large angle (e.g., panel (c) of Figure 3 in Li et al 2023, where this angle is reported to be 125°± 10°). (We note that the empirical cone axis differed from the impact direction by ∼21°, as mentioned in Cheng et al 2023, but this difference does not materially affect the discussion here.) Viewed along the axis of the cone, the ring would appear as a circular annulus while, for any other viewing direction, it would appear as an ellipse.…”
Section: Ejection Mechanismsmentioning
confidence: 80%
“…These skywatchers are among the authors of a study in Nature that describes how the asteroid, named Dimorphos, became temporarily brighter and redder as the spacecraft hit it 1 . One of five papers about the impact published in Nature [1][2][3][4][5] , it describes a real-time view of a cosmic collision -similar to that when Comet Shoemaker-Levy 9 slammed into Jupiter in July 1994.…”
Section: Asteroid Collision Shows How Much Amateur Astronomers Have T...mentioning
confidence: 99%